2002
DOI: 10.1034/j.1399-6576.2002.460816.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pretreatment with ketorolac on propofol injection pain

Abstract: Our results suggested that pretreatment with i.v. 15 and 30 mg ketorolac reduces pain following propofol injection. Moreover, pretreatment with i.v. ketorolac 10 mg with venous occlusion for 120 s achieves the same pain relief effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
2

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 21 publications
2
36
0
2
Order By: Relevance
“…Não houve diferença significativa entre os grupos L e LF na redução da dor causada pela injeção de propofol (68% sem dor versus 70%; p > 0,05) (Figura 1). 14 , mas Scott e col. 17 sugeriram que seja conseqüência da ação de cascata enzimática, possivelmente a cascata da calicreína-cinina. Essa sugestão foi apoiada por Iwama e col. 17 , que demonstraram que o tratamento prévio com um inibidor da calicreína inibia a dor causada pela injeção de propofol.…”
Section: Resultsunclassified
“…Não houve diferença significativa entre os grupos L e LF na redução da dor causada pela injeção de propofol (68% sem dor versus 70%; p > 0,05) (Figura 1). 14 , mas Scott e col. 17 sugeriram que seja conseqüência da ação de cascata enzimática, possivelmente a cascata da calicreína-cinina. Essa sugestão foi apoiada por Iwama e col. 17 , que demonstraram que o tratamento prévio com um inibidor da calicreína inibia a dor causada pela injeção de propofol.…”
Section: Resultsunclassified
“…Niazi et al [18] informed that the pain shall be reduced or delayed only when total infused injection rate is 10-20 sec. Huang et al [19] in their study, indicated that infusing IV liquid through cannulation effects the pain, and also fast moving liquid reduces contact to the vein periphery by diluting propofol and causes less pain. In our study, injection rate is adjusted in a way to administer 40 mg propofol in every 10 minutes, pain incidence inquiry has been performed nearly up to 30 seconds after injection (after 1/4, 2/4 and 3/4 of total propofol dose have been infused) and as this is in accordance with the injection rate specified in literature.…”
Section: Discussionmentioning
confidence: 99%
“…[2,4,[14][15][16][17] Hovewer, even in patients who received most popular lidocaine treatment, the incidence of pain has been reported as frequent as 32%-48%. [15] Propofol is an excellent anesthetic that belongs to the group of phenols, which can irritate the skin, mucous membrane and venous intima.…”
Section: Discussionmentioning
confidence: 99%